PERAN MEDIA SOSIAL DALAM MANAJEMEN STRATEGI LEMBAGA PENDIDIKAN ISLAM(Studi Kasus di MTs Islamic Centre Nahdlatul Wathan) - Muhammad Rozikin; Ria Kurniawaty (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This research aims to analyze the role of social media in increasing the effectiveness of strategic management in Islamic educational institutions, with a case study at MTs Islamic Center Nahdlatul Wathan. The development of digital technology encourages educational institutions to utilize social media as a communication, marketing and community development tool. Using a qualitative approach, data was collected through interviews, observation and documentation, then analyzed using the triangulation method. The research results show that social media plays a significant role in expanding the reach of communication, increasing student and parent involvement, and supporting the promotion of superior programs, which has contributed to an increase in new student enrollment of up to 20% in the last two years. However, challenges such as changing social media algorithms and the need for creative content still need to be addressed. In conclusion, strategic use of social media can increase the visibility and competitiveness of educational institutions, so that continuous adaptation to digital trends is needed for more optimal results.